Reducing administrative costs in US health care: Assessing single payer and its alternatives. (31st March 2021) - Scheinker, David; Richman, Barak D.; Milstein, Arnold; Schulman, Kevin A.
Abstract: Objective: Excess administrative costs in the US health care system are routinely referenced as a justification for comprehensive reform. While there is agreement that these costs are too high, there is little understanding of what generates administrative costs and what policy options might mitigate them. Data Sources: Literature review and national utilization and expenditure data. Study Design: We developed a simulation model of physician billing and insurance‐related (BIR) costs to estimate how certain policy reforms would generate savings. Our model is based on structural elements of the payment process in the United States and considers each provider's number of health plan contracts, the number of features in each health plan, the clinical and nonclinical processes required to submit a bill for payment, and the compliance costs associated with medical billing. Data Extraction: For several types of visits, we estimated fixed and variable costs of the billing process. We used the model to estimate the BIR costs at a national level under a variety of policy scenarios, including variations of a single payer "Medicare‐for‐All" model that extends fee‐for‐service Medicare to the entire population and policy efforts to reduce administrative costs in a multi‐payer model. We conducted sensitivity analyses of a wide variety of model parameters. Principal Findings: Our model estimates that national BIR costs are reduced between 33% and 53% in Medicare‐for‐All style single‐payer models and between 27% and 63% in various multi‐payer models. Under a wide range of assumptions and sensitivity analyses, standardizing contracts generates larger savings with less variance than savings from single‐payer strategies. Conclusion: Although moving toward a single‐payer system will reduce BIR costs, certain reforms to payer‐provider contracts could generate at least as many administrative cost savings without radically reforming the entire health system. BIR costs can be meaningfully reduced without abandoning a multi‐payer system.